Thinking about social problems - Henshel, Richard L. (Harcourt Brace Jovanovich, 2002)
This book adopts an overall social policy approach to the study of social problems. It does not merely enumerate existing conditions - poverty, drug abuse, crime, racism and so forth - though those are continually adduced to discuss larger issues. The focus, rather, is on how we arrrived at various social conditions, what strategies of intervention are available to us and what pitfalls or unexpected consequences we might expect to ensue from those interventions